(untitled) (Tzintzun, Revista de Estudios Históricos, 2021)
The enlisting of African descent soldiers subject to a regime of slavery was made with the promise of freedom, which was written down in different legislations and decrees that were dictated from 1820 onward. This article analyzes how these promises were fulfilled and it is argued that this depended on the ability of the newly freedmen to demonstrate their service in the militia, within a context marked by the pressure of their masters and the political will of the courts and the Peruvian authorities.